An Empirical Study of Automated Teller Machine Users in Oman - Uddin, Mohammed Ahmar; Khan, Mohammed Abdul Imran; Mohammed, Shariq (International Review of Management and Marketing, 2016)
The Omani Banking sector is undergoing significant changes and growth. This study investigated the experiences of Bank Muscat and Bank Dhofar (hereafter BM and BD) customers with Automatic Teller Machines (ATMs) in the Dhofar region of Oman. Primary data was collected from by a random sample of 200 ATM users by means of a semi-structured questionnaire. The data were analyzed using descriptive statistics and t-test. The study found that most of the users were male in the age group of 36-45 having a government job or doing their own business. The study also revealed that the main problems faced by the ATM users are machine out of order, long queue and poor visibility of statement. As regards to the differences between the two banks the study found that significant difference in the mean customer satisfaction between customers of BM and BD for the factor ‘Machine out of order’. Management of these banks must take into account these factors while designing and implementing ATM based policy reforms. Keywords: Automatic Teller Machine (ATM), Bank Muscat, Bank Dhofar, Customer Satisfaction, Challenges, Oman. JEL Classifications: G21, J11, M39, 053